Математичні моделі економічного менеджменту інформаційної безпеки - Levchenko, Y. H.; Demchyshyn, M. V.; Rabchun, A. O. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2011)
The comparative analysis of the quantitative models of economic management of information security is fulfilled. The conditions under which the target functions of the considered models coincide or sufficiently close are set up. The fulfilled calculations illustrate the methodology of quantity determination depending on attack and defense recourses correlation.